2021
DOI: 10.1021/acs.jmedchem.1c01494
|View full text |Cite
|
Sign up to set email alerts
|

Potent Anti-SARS-CoV-2 Activity by the Natural Product Gallinamide A and Analogues via Inhibition of Cathepsin L

Abstract: Cathepsin L is a key host cysteine protease utilized by coronaviruses for cell entry and is a promising drug target for novel antivirals against SARS-CoV-2. The marine natural product gallinamide A and several synthetic analogues were identified as potent inhibitors of cathepsin L with IC50 values in the picomolar range. Lead molecules possessed selectivity over other cathepsins and alternative host proteases involved in viral entry. Gallinamide A directly interacted with cathepsin L in cells and, together wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
83
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 60 publications
(87 citation statements)
references
References 75 publications
4
83
0
Order By: Relevance
“…Introduction of biaryl-substituted MMP moieties at the C-terminus was explored by evaluating analogs 24-33 (Table 3). These compounds possessed either 4-(N-Me)piperidine or N,N-Me2-L-Val at the pseudo-N-terminus and CH2CH2-Ph at the P1 site 24,27 . All but one of the analogs of this series exhibited more potent activity against cruzain compared to gallinamide A.…”
Section: Table 2 Structure−activity Relationships Of Gallinamide a 2-indolyl-mmp Analogs 11-23mentioning
confidence: 99%
See 4 more Smart Citations
“…Introduction of biaryl-substituted MMP moieties at the C-terminus was explored by evaluating analogs 24-33 (Table 3). These compounds possessed either 4-(N-Me)piperidine or N,N-Me2-L-Val at the pseudo-N-terminus and CH2CH2-Ph at the P1 site 24,27 . All but one of the analogs of this series exhibited more potent activity against cruzain compared to gallinamide A.…”
Section: Table 2 Structure−activity Relationships Of Gallinamide a 2-indolyl-mmp Analogs 11-23mentioning
confidence: 99%
“…P. falciparum falcipain enzymes are cathepsin L-like proteases and therefore additional studies showed that gallinamide A is also a potent and highly selective inhibitor of human cathepsin L 22 . The unique linear lipopeptide structure, and potential applicability to proteases of medical relevance, provoked interest in establishing chemical syntheses of gallinamide A and structural analogs 20,[23][24][25][26] . Indeed, gallinamide A has become an attractive starting point for developing selective inhibitors targeting human cathepsin L and other Clan CA cysteine proteases in human pathogens 21,23,24,27 .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations